Barriers to Adoption of Digital Therapeutics (DTx) into Audiology Clinical Practice: Acknowledging the Challenges, Adapting to the Future - Roberts, Melissa J.; Wilson, Wayne J.; Recugnat, Matthieu; Bardy, Fabrice (Seminars in Hearing, 2023)
The continuous advancements in technologies supporting digital health and digital therapeutics (DTx) bring new possibilities to the field of audiology. This study considers a new DTx for tinnitus called Tinnibot and the willingness of a group of Australian university audiology students to consider this new DTx in their future careers as practicing audiologists. A single-group case-series design (pretest/posttest) was used to examine the opinions of 10 university audiology students before and after participating in a 2-hour information workshop on the topics of tinnitus, DTx, cognitive behavioral therapy, and a new digital therapy tool for tinnitus called Tinnibot. Student knowledge levels of the main topic areas increased from poor (before the workshop) to moderate to high after the workshop, with 40% of participants reporting they would very likely use digital therapies for future patients. A common barrier to improving this rating was the need for direct hands-on training on the DTx before the students would be confident to recommend the DTx to patients. Incorporating direct training on DTx into university audiology programs would allow greater uptake of DTx by students as they begin their careers as practicing audiologists.
Keywords: digital therapeutics; tinnitus; educational workshop